Relationships between Early Life Victimization, Antisocial Traits, and Sexual Violence: Executive Functioning as a Mediator. Issue 6 (18th August 2019) - Yoder, Jamie; Grady, Melissa D.; Precht, Madison
ABSTRACT: Few research studies examine how the relationship between trauma and executive functioning can influence sexual violence among youth. Knight and Sims-Knight (2004) proposed a Developmental Etiological Theory (DET) connecting early life physical and sexual victimization to sexual violence via antisocial traits. Drawing from research that identifies a link between early life victimization and executive functioning, this study tests an adaptation to the DET by including executive functioning as an intervening factor. Using data on adolescents adjudicated of sexual and non-sexual crimes in a western state ( N = 200), multiple structural equation models tested direct and indirect relationships between early life sexual, physical victimization, and other adversity, four differential forms of executive functioning, callousness, and sexual violence. Results revealed statistically significant direct pathways between variables of interest and a multi-meditational effect of certain forms of executive functioning and callousness in the relationship between victimization and sexual violence. Treatment and research implications are discussed.